Group problem-solving and decision-making - Larson Jr., James R. (Henry Stewart Talks, 2013)
Reasons for using groups, A continuum of group tasks, Conceptualizing performance gains in groups, Additive vs. synergistic performance gains, Two barriers to performance gains in groups, Concentrated preferences, Unevenly distributed information